Bio-based composition and application thereof as paper-plastic pulp additive
Patent Information
- Application Number
- CN202411486478.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-07
AI Technical Summary
一方面会严重影响产品的机械强度,另一方面会导致浆料的保水性提高,造成成型工序的脱水更慢更困难,从而导致成型工序的湿胚水分含量高,需要消耗更多的热能烘干
[0033]本发明提供的生物基组合物用于纸浆模塑生产,能够有效提升纸塑的物理强度指标,例如环压强度、撕裂强度、耐破度和/或抗张强度。还可以避免粘模和堵塞模孔,提高生产效率。
Smart Images

Figure CN119266004A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of pulp additives, and in particular relates to a bio-based composition and an application thereof as a paper and plastic pulp additive. Background Art
[0002] For a long time, the pulp molding industry has had the following pain points that need to be addressed:
[0003] 1. Raw material limitation, 2. Low production efficiency, 3. Insufficient mechanical strength.
[0004] Specifically, most companies currently use bamboo pulp and bagasse pulp in a ratio of 7:3 or 6:4 to produce paper plastics. In addition to cost factors, the main reason for not adding wood pulp is that the shrinkage rate of wood pulp fibers is high, which has a great impact on the dimensional stability of paper plastic products. For example, when using grass fiber raw materials such as bamboo pulp and bagasse pulp, the fine components in the grass fiber raw materials are not fine fibers that fall off during the fiber fibrillation process, but mostly various miscellaneous cells. On the one hand, it will seriously affect the mechanical strength of the product, and on the other hand, it will lead to an increase in the water retention of the pulp, causing the dehydration of the molding process to be slower and more difficult, resulting in a high moisture content of the wet embryo in the molding process, which requires more heat energy to dry.
[0005] Pulp molded products (hereinafter referred to as paper plastics) are made of fiber as the main raw material (such as wood, bagasse or bamboo) and are formed by hot pressing in molding molds. Auxiliary materials such as reinforcing agents, sizing agents, water repellents, coatings, mineral fillers, etc. are usually added during production. The addition of these auxiliary materials will cause mold sticking and clogging of mold holes, resulting in frequent mold removal and cleaning, affecting production efficiency. Summary of the invention
[0006] In order to improve the above technical problems, the present invention provides a bio-based composition, comprising:
[0007] Component A: one or both selected from biomass materials or cationized biomass materials; both the biomass materials and cationized biomass materials have a dendritic, fibrous, flaky, feathery, flocculent or porous sponge-like structure;
[0008] Component B: one, two or more selected from PHA (polyhydroxyalkanoate), AKD (alkyl ketene dimer), PGA (polyglycolic acid), PLA (polylactic acid), PBAT (polybutylene terephthalate-adipate), cellulose ester and cellulose ether;
[0009] Component C: retention aid;
[0010] The bio-based composition does not contain reinforcing agents, sizing agents and / or mineral fillers.
[0011] According to one embodiment of the present invention, the bio-based composition consists of component A, component B and component C.
[0012] According to an embodiment of the present invention, the cationized biomass material may be selected from biomass materials modified with glycidyltrimethylammonium chloride or 3-chloro-2-hydroxypropyl-trimethylammonium chloride.
[0013] According to an embodiment of the present invention, the reinforcing agent includes but is not limited to dry / wet reinforcing agents known in the art, such as PAM (polyacrylamide), PAE (polyamide polyamine epichlorohydrin), UF (urea-formaldehyde resin), MF (melamine formaldehyde resin), etc.
[0014] According to an embodiment of the present invention, the sizing agent is a starch material, including but not limited to cassava starch, corn starch, pregelatinized starch and oxidized starch, cationic starch, phosphate starch, acetate starch, enzyme hydrolyzed starch, etc.
[0015] According to an embodiment of the present invention, the mineral filler includes but is not limited to calcium carbonate, talc, kaolin, wollastonite, aluminum hydroxide, magnesium hydroxide and the like.
[0016] According to an embodiment of the present invention, the retention aid is selected from one, two or more of silica sol, alum, polyethylene oxide, polyethylene imine and the like.
[0017] According to an embodiment of the present invention, the weight ratio of component A, component B and component C is 1:(0.1-0.2):(0.1-0.2).
[0018] According to an embodiment of the present invention, the bio-based composition further comprises a dispersant, for example, the dispersant is water. Further, the ratio of the weight of the dispersant to the sum of the weights of the other components (component A, component B and component C) is 1:(0.125-0.2).
[0019] According to one embodiment of the present invention, the bio-based composition consists of the following components in parts by weight:
[0020] 100 parts of a dispersion containing component A, wherein the weight fraction of component A is 1 to 10 wt %;
[0021] A dispersion containing 3.5-10 parts of component B, wherein the weight fraction of component B is 10-30wt%;
[0022] A dispersion containing 0.5-2 parts of component C, wherein the mass fraction of component C is 20-35wt%;
[0023] Preferably, the dispersant used in each dispersion is water.
[0024] For example, the bio-based composition consists of the following components in parts by weight:
[0025] 100 parts of a dispersion containing component A, wherein the weight fraction of component A is 2 wt% of a cationic biomass material;
[0026] 5 parts of a dispersion containing component B, wherein the weight fraction of component B is 19 wt % of cellulose ether;
[0027] 1 part of a dispersion containing component C, wherein component C is a silica sol with a mass fraction of 30 wt%;
[0028] Preferably, the dispersant used in each dispersion is water.
[0029] The present invention also provides the use of the above bio-based composition in the preparation of paper and plastic pulp, preferably as a paper and plastic pulp reinforcing additive.
[0030] According to an embodiment of the present invention, the pulp includes but is not limited to wood pulp and / or grass pulp, for example, one, two or more of coniferous wood pulp, broadleaf wood pulp, bamboo pulp, bagasse pulp, reed pulp, straw pulp, etc. produced by various pulping methods, exemplified by bamboo pulp and bamboo-bagasse mixed pulp.
[0031] According to an embodiment of the present invention, the weight ratio of the bio-based composition to bone dry pulp is (2-6):100, for example 4:100.
[0032] Beneficial Effects
[0033] The bio-based composition provided by the present invention is used in pulp molding production, which can effectively improve the physical strength indexes of paper molding, such as ring crush strength, tear strength, bursting resistance and / or tensile strength. It can also avoid mold sticking and mold hole clogging, thereby improving production efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a scanning electron microscope image of the biomass material with a dendritic or flocculent structure used in Example 1.
[0035] Figure 2 The left picture in the figure is a scanning electron microscope image of the cationized biomass material with a dendritic or floc structure used in Example 3, and the right picture is a scanning electron microscope image of the cationized biomass material with a dendritic or floc structure used in Example 2.
[0036] Figure 3 Pictures of an unblocked mold (left) and a blocked mold (right). DETAILED DESCRIPTION
[0037] [Structures of Biomass Materials and Cationized Biomass Materials]
[0038] According to an embodiment of the present invention, the cationized biomass material may be selected from biomass materials modified with glycidyltrimethylammonium chloride or 3-chloro-2-hydroxypropyl-trimethylammonium chloride.
[0039] According to an embodiment of the present invention, the biomass material may be a regenerated natural polymer (eg, type II cellulose, or a mixture of type II cellulose and type I cellulose).
[0040] According to an embodiment of the present invention, the biomass material and the cationized biomass material may have a structure I with a size (i.e., volume average size) of 5 μm to 500 μm, preferably 10 μm to 400 μm, and further preferably, the size of the micron-sized structure is 30 μm to 300 μm, for example, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm , 135μm, 140μm, 145μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm, 300μm, 350μm, 400μm, 450μm, 500μm, or any point value among any two points or any intermediate value formed by any two points.
[0041] According to an embodiment of the present invention, the biomass material and the cationized biomass material may also have a structure II with a length of 500nm to 1500nm, preferably a length of 700nm to 1200nm, and further preferably a length of 800nm to 1000nm, for example, any value among 500nm, 600nm, 700nm, 800nm, 900nm, 1000nm, 1100nm, 1200nm, 1300nm, 1400nm, 1500nm or any point value in the middle value formed by any two point values.
[0042] According to an embodiment of the present invention, the diameter of the structure II is 50nm to 800nm, preferably 100nm to 500nm, for example, any value among 150nm, 200nm, 300nm, 400nm, 500nm, 600nm or any point value in the middle value formed by any two point values.
[0043] According to an embodiment of the present invention, the aspect ratio of the structure II is 1:1 to 1:150, preferably 1:1 to 1:100, more preferably 1:10 to 1:100, for example 1:50.
[0044] According to an embodiment of the present invention, the structure I includes at least one of micron sheets, micron fibers and micron multi-level structures.
[0045] According to an embodiment of the present invention, the structure I is fibrous or film-like, which can also be called fiber-like.
[0046] According to an embodiment of the present invention, the structure II is distributed on the surface and / or edge of the structure I. Specifically, the structure II is densely distributed on the surface and / or edge of the structure I.
[0047] According to an embodiment of the present invention, the structure II is distributed on the structure I to form a flocculent shape as a whole.
[0048] According to an embodiment of the present invention, the structure II is distributed on the structure I to form an overall structure similar to a porous sponge.
[0049] According to an embodiment of the present invention, the structure II and the structure I together form a feather-like structure.
[0050] According to an embodiment of the present invention, the structure II and the structure I together form a dendritic structure.
[0051] According to an embodiment of the present invention, the structure II is in the shape of villi, tentacles, whiskers or other irregular structures.
[0052] According to an embodiment of the present invention, the biomass material and the cationized biomass material are in a fibrous, flaky, feathery, dendritic, flocculent or porous sponge-like structure.
[0053] The key to the full performance of the bio-based composition is retention.
[0054] The main components in the bio-based composition, after being cationized, can give the bio-based composition the following effects:
[0055] 1. Improve its own retention rate, thereby exerting a multiplier effect;
[0056] 2. Improve the adsorption and bonding strength between fibers;
[0057] 3. Improve the retention of fine components in straw pulp raw materials.
[0058] In principle, the prepared pulp raw materials for papermaking contain cellulose of different proportions and lengths. In the product, long and short fibers play their respective roles. Whether it is paper or paper plastic, the process of product formation is the process of long and short fibers overlapping each other to form a filter layer when the pulp is filtered. Due to this loose and porous overlapping structure, a large number of fine components will be lost into the white water circulation system. The proportion of fine components (fine fibers and fillers) retained in the filter layer is called retention rate. The one-way retention rate and the cleanliness of white water are indicators that are of great concern in production.
[0059] The retention of fine components depends on mechanical interception and electrostatic adsorption. To improve the mechanical interception, long fibers must be refined, that is, they must be ground at a specific concentration (since the refining rate of straw pulp is very low and will further increase the number of fine components), so the refining method is not easy to implement in paper and plastic production. Since pulp fibers are negatively charged, it is undoubtedly a very good choice to improve electrostatic adsorption by modification, especially for components with micro-nano particle sizes.
[0060] The biomass material involved in the present invention has an ultra-fine particle size and a rich dendritic or network-like microstructure, and has a high density of bonding contacts. There are multiple contacts that can produce effective bonding on a single fiber, so the proportion of the biomass material retained in the final product is increased, which will double the effect of its function.
[0061] [Preparation of biomass materials]
[0062] A method for preparing a biomass material, wherein the method is selected from method A or method B, wherein method A comprises the following steps:
[0063] dissolving the biomass in a solvent to form a biomass solution;
[0064] The biomass solution and the coagulation bath are added to a crushing device, and the two are mechanically crushed while being mixed to prepare the bio-based material; or after the mechanical crushing, the biomass material is prepared by filtering and washing;
[0065] The method B comprises the following steps: pouring a biomass solution into a coagulation bath to form a biomass gel; and subjecting the biomass gel to micro-nano treatment by mechanical crushing to obtain the biomass material.
[0066] According to an embodiment of the present invention, the reagent used in the washing step in method A and method B is selected from at least one of water, alcohol, alcohol-water mixture, HCl aqueous solution, NaOH aqueous solution, and inorganic salt aqueous solution, preferably water and / or alcohol, such as water.
[0067] According to an embodiment of the present invention, the biomass is derived from one, two or more of the following substances: cellulose or its derivatives, chitosan or its derivatives, chitin, alginate, lignin, glucan, hemicellulose, straw, plant stems and leaves, reeds, bagasse, Chinese medicine residues, tea residues, corn cobs, fruit shells, vines, branches. For example, the biomass is selected from at least one of microcrystalline cellulose, bacterial cellulose, lignin, cotton pulp, wood pulp, bamboo pulp, grass pulp, refined cotton, cotton wool, cotton linters, bagasse, wood and straw, etc.; preferably, one or more of microcrystalline cellulose, refined cotton, cotton wool and wood pulp.
[0068] According to an embodiment of the present invention, the solvent for dissolving the biomass can be selected from any good solvent known in the art that can completely dissolve the biomass. Preferably, according to the different types of cellulose or cellulose-containing raw materials, the selected solvent can be selected from one or more of the following systems: organic solvents, ionic liquids, mixed solvents of ionic liquids and organic solvents, choline-type ionic liquid low eutectic solvent systems, organic solvent / salt systems, amine oxide systems (NMMO), carbamate systems, alkali / water systems, alkali / urea systems, alkali / thiourea systems, liquid ammonia / NH4SCN, organic acids, aqueous solutions of metal salts, alcohol solutions of metal salt hydrates, water-alcohol mixed solutions of metal salt hydrates, and other solvent systems.
[0069] According to an embodiment of the present invention, the coagulation bath is selected from at least one of water, alcohol, alcohol-water mixture, HCl aqueous solution, NaOH aqueous solution, and inorganic salt aqueous solution, preferably water and / or alcohol, such as water.
[0070] For example, the biomass material can be obtained by the preparation method described in Chinese Patent Application No. 202310481795.1.
[0071] [Method for preparing cationized biomass material]
[0072] The preparation method of the cationic biomass material comprises: adding an alkaline aqueous solution, such as NaOH or KOH aqueous solution, to a biomass solution, stirring and dissolving to obtain a biomass alkali solution, adding an alcohol organic solvent to the biomass alkali solution to dissolve, adding a cationic etherifying agent to carry out a grafting reaction, and washing with deionized water to neutrality, thereby obtaining a cationic biomass material.
[0073] According to an embodiment of the present invention, the concentration of the alkaline aqueous solution is 0.1% to 3%.
[0074] According to an embodiment of the present invention, the mass concentration of the biomass material in the alkaline solution is 2% to 10%.
[0075] According to an embodiment of the present invention, the cationic etherifying agent is selected from organic amine salts containing halogenated hydrocarbon groups or epoxy groups, for example, one or more of glycidyltrimethylammonium chloride and 3-chloro-2-hydroxypropyltrimethylammonium chloride.
[0076] According to an embodiment of the present invention, the organic solvent may be one or a composite solvent of methanol, ethanol, isopropanol.
[0077] According to an embodiment of the present invention, the weight ratio of the cationic etherifying agent to the biomass material is 1:(0.8-1.2), for example 1:1.
[0078] According to an embodiment of the present invention, the reaction temperature is 25-70°C, such as 25°C, 30°C, 40°C, 50°C or 60°C.
[0079] According to an embodiment of the present invention, the reaction time is 2 to 48 hours, such as 4 to 24 hours.
[0080] According to an embodiment of the present invention, the reaction is carried out under stirring conditions.
[0081] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.
[0082] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0083] Example 1
[0084] The bio-based composition comprises the following components in parts by weight:
[0085] 100 parts of a dispersion containing component A, wherein component A is a biomass material having a dendritic structure, and the mass fraction of the biomass material is 2 wt%;
[0086] 5 parts of a dispersion containing component B, wherein component B is AKD with a mass fraction of 19wt%;
[0087] Component C1 is a retention aid silica sol, and the mass fraction of the silica sol is 30wt%.
[0088] Preparation of the bio-based composition: 19 wt% of AKD emulsion and retention aid were added to the dispersion containing component A, mixed thoroughly and stirred for 30 minutes.
[0089] Biomass materials with dendritic structures such as Figure 1As shown, it includes a main structure and tentacle-like branch structures: the main structure is about 330 μm in size; the tentacle-like branch structures are distributed on the main structure, with diameters ranging from 50 to 800 nm.
[0090] Preparation of dispersion containing component A:
[0091] 6 g of bacca wood pulp was added to a three-necked flask, and 94 g of 1-ethyl-3-methylimidazolium chloride ionic liquid ([EMIM][Cl]) was added, and the mixture was stirred at 80°C for 2 h to obtain a cellulose solution. The cellulose solution and deionized water were added to a toothed rotor type colloid mill at a volume ratio of 1:10 to grind the mixture. After grinding for 30 minutes, a broken gel was obtained, which was filtered and repeatedly washed with water until no precipitation was produced when AgNO3 was added to the filtrate, and the filtered gel was dispersed with water again.
[0092] Application Example 1
[0093] Bio-based composites for the production of pure bamboo chemical pulp, paper and plastic products
[0094] Compared with bagasse pulp and straw pulp, bamboo pulp is characterized by long and thin fibers. When it is used alone in paper and plastic production, the resulting product will have low density and easy fluffing on the surface, which is similar to pure hardwood pulp. This is also an important reason for the use of bamboo pulp and bagasse pulp. Based on this situation, this application example uses the bio-based composition of Example 1 for targeted formula addition, and the steps are as follows:
[0095] 1. Use a fiber disintegrator to fully and evenly disperse the natural pure bamboo pulp produced by the chemical method, with a beating degree of about 22°SR, and add water to prepare a 0.3wt% pulp mixture for standby use.
[0096] 2. Slowly add the bio-based composition of Example 1 to the reserved 100 parts of pulp mixture, stirring while adding, and continue stirring for no less than 30 minutes after all the pulp is added. After slurry is prepared according to the above method, a mold is used for processing (hot pressing temperature 200°C, -0.06MP vacuum negative pressure) into a paper-plastic product, which is recorded as sample 1#.
[0097] Two groups of comparative samples were set up at the same time, and the only difference from sample 1# was the formula: sample 2# was prepared without adding the bio-based composition component, and sample 3# was prepared by replacing the bio-based composition with 1.5% wet strength agent PAE. Refer to GB / T 2679.8-2016 Determination of ring crush strength of paper and paperboard
[0098] GB / T 455-2002 Paper and paperboard tear resistance test standard
[0099] GB / T 1539-2007 Test standard for the bursting strength of paperboard
[0100] GB / T 12914-2008 Paper and paperboard tensile strength test standard tests the relevant physical strength indicators of each sample. The test results are shown in Table 1 below.
[0101] Table 1
[0102]
[0103]
[0104] From the data in the table, it can be seen that the addition of the bio-based composition improves the physical strength of pure bamboo chemical pulp paper and plastic products, and the degree of improvement is higher than the strengthening effect of conventional wet strength agents (PAE dosage 1.5%).
[0105] Example 2
[0106] The difference from Example 1 is that the biomass material in Example 2 is a cationized biomass material, and the main body size before cationization treatment is about 330 μm, and the specific morphology is as follows: Figure 2 As shown in the figure on the right, the specific preparation of the cationic biomass material is as follows:
[0107] 1. Add 6g of bacca wood pulp to a three-necked flask, add 94g of 1-ethyl-3-methylimidazolium chloride ionic liquid ([EMIM][Cl]), and stir at 80°C for 2h to obtain a cellulose solution. Add the cellulose solution and deionized water to a toothed rotor colloid mill at a volume ratio of 1:10 and grind them. After grinding for 30 minutes, a broken gel is obtained. After filtering, it is repeatedly washed with water until no precipitation is produced when AgNO3 is added to the filtrate. The filtered gel is re-dispersed with water. Weigh 5% of the absolute dry weight of cellulose with NaOH and add it to the system, stirring for 60min. After the reaction is completed, wash with deionized water until it is neutral.
[0108] 2. Weigh glycidyl trimethyl ammonium chloride in a ratio of 1:1 to the absolute dry weight of cellulose and glycidyl trimethyl ammonium chloride, and dissolve it in an appropriate amount of isopropanol to obtain an isopropanol solution of glycidyl trimethyl ammonium chloride. After the solution system in step 1 is processed, pour the above solution.
[0109] 3. Reaction temperature and time: 50°C, 6h.
[0110] 4. After the reaction is completed, wash with deionized water until it is neutral.
[0111] Application Example 2
[0112] Example of production process of bio-based composites for pure bamboo chemical mechanical pulp paper and plastic products
[0113] Compared with pure bamboo chemical pulp, pure bamboo chemical mechanical pulp has a higher pulp yield and lower comprehensive cost, but its fiber purification degree is not as good as chemical pulp. The characteristics of this pulp are that the fiber stiffness is slightly better, but the content of fine components and miscellaneous cells is relatively high. When it is used alone in paper and plastic production, the resulting product will have a high degree of tightness and insufficient surface smoothness. Based on this situation, this application example uses the bio-based composition of Example 2 for targeted formula addition, and the steps are as follows:
[0114] 1. Use a fiber disintegrator to fully and evenly disperse the natural color pure bamboo chemical pulp, with a beating degree of about 25°SR, and add water to prepare a 0.3wt% pulp mixture for standby use.
[0115] 2. Slowly add the bio-based composition of Example 2 and 1 part of anionic garbage collector into 100 parts of the reserved pulp mixture, stirring while adding, and continue stirring for not less than 30 minutes after all are added.
[0116] After slurrying according to the above method, the paper-plastic product was processed using a mold (hot pressing temperature 200°C, -0.06MP vacuum negative pressure), which was recorded as sample A#.
[0117] Three groups of comparative samples were set up at the same time, and the only difference from sample A# was the different formulas: sample B# was prepared from the formula of non-cationized bio-based composition components, sample C# was prepared from the formula without adding bio-based composition components, and sample D# was prepared from the formula of replacing the bio-based composition with 1.5% wet strength agent PAE.
[0118] Refer to GB / T 2679.8-2016 Determination of ring crush strength of paper and paperboard
[0119] GB / T 455-2002 Paper and paperboard tear resistance test standard
[0120] GB / T 1539-2007 Test standard for the bursting strength of paperboard
[0121] GB / T 12914-2008 Paper and paperboard - Determination of tensile strength
[0122] The relevant physical strength indicators of each sample were tested respectively, and the test results are shown in Table 2 below.
[0123] Table 2
[0124]
[0125] From the data in the table, it can be seen that the addition of the cationic modified bio-based composition greatly improves the physical strength of pure bamboo chemical mechanical pulp paper and plastic products, and the improvement of various strength indicators is significantly higher than the improvement effect of conventional wet strength agent (PAE dosage 1.5%).
[0126] Example 3
[0127] The difference from Example 2 is that the size of the cationized biomass material is about 179 μm, and the specific morphology is as follows: Figure 2 As shown in the left figure. The specific preparation of the cationic biomass material is as follows:
[0128] 1. Add 4g of bacca wood pulp to a three-necked flask, add 94g of 1-allyl-3-methylimidazolium chloride ionic liquid ([AMIM][Cl]), and stir at 80°C for 2h to obtain a cellulose solution. Add the cellulose solution and ethanol to a cone rotor colloid mill at a volume ratio of 1:100 and grind them. After grinding for 30 minutes, a broken gel is obtained. After filtering, it is repeatedly washed with water until no precipitation is produced when AgNO3 is added to the filtrate. The filtered gel is re-dispersed with water. Weigh 5% of the absolute dry weight of cellulose with NaOH and add it to the system, stirring for 60min. After the reaction is completed, wash with deionized water until it is neutral.
[0129] 2. Weigh glycidyl trimethyl ammonium chloride in a ratio of 1:1 to the absolute dry weight of cellulose and glycidyl trimethyl ammonium chloride, and dissolve it in an appropriate amount of isopropanol to obtain an isopropanol solution of glycidyl trimethyl ammonium chloride. After the solution system in step 1 is processed, pour the above solution.
[0130] 3. Reaction temperature and time: 50°C, 6h.
[0131] 4. After the reaction is completed, wash with deionized water until it is neutral.
[0132] Application Example 3
[0133] Example of production process of bio-based composites for bamboo-bagasse mixed pulp paper-plastic products
[0134] At present, most companies use bamboo pulp and bagasse pulp in a ratio of 7:3 or 6:4 to produce paper plastic. Although this ratio can better balance the long and short fiber fractions, the strength is still not ideal.
[0135] This application example uses the bio-based composition of Example 3 for targeted formulation addition, and the steps are as follows:
[0136] 1. Use a fiber disintegrator to mix bleached bamboo pulp and bagasse pulp in a ratio of 7:3, fully and evenly disperse them, with a beating degree of about 22°SR, and add water to prepare a 0.3wt% pulp mixture for standby use.
[0137] 2. Slowly add the bio-based composition of Example 3 and 1 part of anionic garbage collector into 100 parts of the reserved pulp mixture, stirring while adding, and continue stirring for not less than 30 minutes after all are added.
[0138] After slurrying according to the above method, the paper-plastic product was made using a mold (hot pressing temperature 200°C, -0.06MP vacuum negative pressure), which was recorded as sample I#.
[0139] Three groups of comparative samples were set up at the same time, and the only difference from sample I# was the different formula: sample II# was prepared from the formula of non-cationized bio-based composition components, sample III# was prepared from the formula without adding bio-based composition components, and sample IIII# was prepared from the formula with 1.5% wet strength agent PAE replacing the bio-based composition. The samples were prepared according to GB / T2679.8-2016 Determination of Ring Compression Strength of Paper and Paperboard
[0140] GB / T 455-2002 Paper and paperboard tear resistance test standard
[0141] GB / T 1539-2007 Test standard for the bursting strength of paperboard
[0142] GB / T 12914-2008 Paper and paperboard - Determination of tensile strength
[0143] The relevant physical strength indicators of each sample were tested respectively, and the test results are shown in Table 3 below.
[0144] Table 3
[0145]
[0146] At the same time, the slurry containing the bio-based composition of Examples 1-3 does not contain reinforcing agents, starch-based substances and mineral fillers, so when used in paper and plastic production, it avoids sticking to the mold and clogging the mold holes (such as Figure 3 The left picture shows the mold when using the slurry produced by the bio-based composition of the embodiment, and the right picture shows the mold when using the slurry containing reinforcing agent, starch-like substance and mineral filler). There is no need to frequently remove the mold for cleaning, which improves production efficiency.
[0147] When biomass materials with fibrous, flaky, feathery, flocculent or porous sponge-like structures are used to replace the biomass materials in Application Examples 1-3, the improvement of the physical strength of the paper-plastic product has the same or similar effect as shown in Application Examples 1-3.
[0148] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A bio-based composition, characterized in that The bio-based composition comprises: Component A: one or both selected from biomass materials or cationized biomass materials; both the biomass materials and cationized biomass materials have a dendritic, fibrous, flaky, feathery, flocculent or porous sponge-like structure; Component B: one, two or more selected from PHA (polyhydroxyalkanoate), AKD (alkyl ketene dimer), PGA (polyglycolic acid), PLA (polylactic acid), PBAT (polybutylene terephthalate-adipate), cellulose ester and cellulose ether; Component C: retention aid; The bio-based composition does not contain reinforcing agents, sizing agents and / or mineral fillers.
2. The bio-based composition according to claim 1, characterized in that The bio-based composition consists of component A, component B and component C.
3. The bio-based composition according to claim 1 or 2, characterized in that The cationized biomass material is selected from biomass materials modified with glycidyltrimethylammonium chloride or 3-chloro-2-hydroxypropyltrimethylammonium chloride.
4. The bio-based composition according to any one of claims 1 to 3, characterized in that The reinforcing agent includes but is not limited to PAM (polyacrylamide), PAE (polyamide polyamine epichlorohydrin), UF (urea-formaldehyde resin) and / or MF (melamine formaldehyde resin); And / or, the sizing agent is a starch material, including but not limited to cassava starch, corn starch, pregelatinized starch and oxidized starch, cationic starch, phosphate starch, acetate starch and / or enzyme hydrolyzed starch; And / or, the mineral filler includes but is not limited to calcium carbonate, talc, kaolin, wollastonite, aluminum hydroxide and / or magnesium hydroxide.
5. The bio-based composition according to any one of claims 1 to 3, characterized in that The retention aid is selected from one, two or more of silica sol, alum, polyethylene oxide and polyethylene imine.
6. The bio-based composition according to any one of claims 1 to 5, characterized in that The weight ratio of component A, component B and component C is 1:(0.1-0.2):(0.1-0.2).
7. The bio-based composition according to any one of claims 1 to 6, characterized in that The bio-based composition also includes a dispersant, water.
8. The bio-based composition according to claim 7, characterized in that The ratio of the weight of the dispersant to the sum of the weights of the other components (component A, component B and component C) is 1:(0.125-0.2).
9. Use of the bio-based composition according to any one of claims 1 to 8 in the preparation of paper and plastic pulp, preferably as a paper and plastic pulp reinforcing additive.
10. The use according to claim 9, characterized in that: The pulp includes, but is not limited to, wood pulp and / or grass pulp, such as one, two or more of coniferous wood pulp, broadleaf wood pulp, bamboo pulp, bagasse pulp, reed pulp and straw pulp.
Citation Information
Patent Citations
Biomass-based reinforcing agent for paper and application of biomass-based reinforcing agent
CN121473165A
Bio-based barrier composition and preparation method thereof, composition for preparing paper pulp molded product and paper pulp molded product
CN117536012A
Method for improving grease resistance and oil resistance of fiber-based articles
CN118369479A
Colloid mill for preparing biomass-based material
CN220547061U
Molded pulp article and processes for making them
WO2023180808A2
Cited By
Acid-neutral nano PHA paperboard reinforcing agent as well as preparation and application thereof
CN121295549A
Acid-neutralizing nanopha paperboard enhancer and preparation and application thereof
CN121295549B